Synthesis of novel benzimidazole containing antimicrobial peptides (AMPs) with significant inhibitory effect on multidrug resistant strain of Salmonella typhimurium. Issue 23 (2nd December 2021) - Aamra, Husena; Khan, Farooq-Ahmad; Jahan, Humera; Zafar, Munira; Ali, Hunain; Shaheen, Farzana
Abstract: Multiple drug resistance (MDR) of bacterial infections is a serious public health concern, since the currently available antibiotics are less effective and nonspecific. Antimicrobial peptides (AMPs) are promising alternative to the conventional antibiotics, as they can easily interact with bacterial peptidoglycan (PGN) through penetration or dissolving the biofilms with minimal side-effects. Herein, we report a simple and scalable method for the synthesis of benzimidazole containing peptides, with significant inhibitory effect by compound 3 (IC50 = 37 ± 1.9 µM) on multidrug resistant strain of Salmonella typhimurium . Graphical Abstract: UF0001